2023
DOI: 10.3390/app13179829
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Vibration Characteristics of Cross-Type Hydraulic Pipeline Based on Finite Element Method

Zhe Liu,
Huiping Li,
Baichun Li
et al.

Abstract: Branched hydraulic lines are prone to leakage and break under complex working conditions. The coupling vibration problem caused by the fluid pressure beat and external mechanical excitation of the pump at the junction of the branch of the cross-type hydraulic pipeline is very common. So a method combining finite element simulation and fluid-structure interaction vibration experiments is proposed for research. First, the possibility of the finite element method in solving the pipeline vibration problem is verif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This model contains two transport equations, namely, turbulent kinetic energy k and turbulent dissipation ε . The equations are as follows (Liu et al , 2023; Liaghat et al , 2014): where G k denotes the turbulent kinetic energy generated by the laminar velocity gradient; G b denotes the turbulent kinetic energy generated by buoyancy; Y M denotes the contribution term of the turbulent expansion in the compressible flow to the global flow to the dissipation term; C 1 , C 2 and C 3 denote constants; σ k and σ ε denote the turbulent Prandtl numbers in the k equation and ε equation, respectively; µ t denotes the turbulent viscosity; and S k and S ε denote the user-defined turbulent kinetic energy term and turbulent dissipation source term, respectively.…”
Section: Simulation Scheme and Model Simplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This model contains two transport equations, namely, turbulent kinetic energy k and turbulent dissipation ε . The equations are as follows (Liu et al , 2023; Liaghat et al , 2014): where G k denotes the turbulent kinetic energy generated by the laminar velocity gradient; G b denotes the turbulent kinetic energy generated by buoyancy; Y M denotes the contribution term of the turbulent expansion in the compressible flow to the global flow to the dissipation term; C 1 , C 2 and C 3 denote constants; σ k and σ ε denote the turbulent Prandtl numbers in the k equation and ε equation, respectively; µ t denotes the turbulent viscosity; and S k and S ε denote the user-defined turbulent kinetic energy term and turbulent dissipation source term, respectively.…”
Section: Simulation Scheme and Model Simplificationmentioning
confidence: 99%
“…The results indicate that the guide vane can effectively reduce the vibration and flow-induced noise of the bend in the 90° bend, and the ideal position of the guide vane is determined. Liu et al (2023) examined the vibration of a cross-shaped branch pipe under fluid pressure fluctuation and external excitation via a single-phase fluid-solid coupling method. The results indicated that the first-, second- and fifth-order modal frequencies of the cross-shaped tube are more likely to resonate with the external pressure excitation, and the vibration direction is in the X- direction.…”
Section: Introductionmentioning
confidence: 99%